Time variation in macro-financial linkages - Esteban Prieto; Sandra Eickmeier; Massimiliano Marcellino (Deutsche Bundesbank, 2013)
We analyze the contribution of credit spread, house and stock price shocks to GDP growth in the US based on a Bayesian VAR with time-varying parameters estimated over 1958-2012. Our main findings are: (i) The contribution of financial shocks to GDP growth fluctuates from about 20 percent in normal times to 50 percent during the global financial crisis. (ii) The Great Recession and the subsequent weak recovery can largely be traced back to negative housing shocks. (iii) Housing shocks have become more important for the real economy since the early-2000s, and negative housing shocks are more important than positive ones.
Keywords: C32; E5; E3; 330; financial shocks; time-varying parameter VAR model; Global Financial Crisis; macro-financial linkages